(untitled) (Ozone Therapy Global Journal, 2016)
Introduction: Coronary heart failure represents the end stage of ischemic, valvular or hypertensive heart disease, having become a first-rate care problem in developed countries, making this syndrome one of cardiovascular epidemics of the century, as despite of all scientific treatments are not sufficient for the control and prevention of this disease. Objective: To determine the effect of the ozone therapy in the chronic heart failure. Method: a study was carried out in a total of 30 patients with left chronic deficiency of the heart with dysfunction systolic ventricular degree II and III according to the definition of the Association of the Heart of New York that went to the consultation of the section of heart deficiency of the department of Transplant of the Heart and Service of cardiovascular surgery in the Hospital Hermanos Ameijeiras, in City of the Havana, Cuba, in the period from January of 2010 until December of 2012; the sample was divided in two groups of 15 patients each one, a group study that was treated with 32 applications of autohaemotherapy with ozone, twice a week, as helping of the conventional pharmacological therapy and a control group only with conventional pharmacological therapy. The evaluated parameters were Quality of Life for EUROQOL-5 D, the Functional Class of the NYHA and Oxygen Consumption by ergometric test, and the Ejection Fraction calculated by echocardiography. The evaluations were made before and after the treatments. Results: The obtained results were compared by means of the test of Fisher with the statistical method Fisher’s Exact Test for Count it Dates and for calculations of the intervals of trust for proportions being proven that the group tried with ozone had an answer significantly better than the group control in all the evaluated parameters; adverse events were not presented during the treatments. Conclusions: the autohaemotherapy with ozone was useful, beneficial and sure as helping in the control of left chronic deficiency of the heart with dysfunction systolic ventricular degree II and III according to the definition of the Association of the Heart of New York